ARTICLE RETRACTED DUE TO PLAGIARISM BY THE AUTHOR Comprehensive development of physical qualities of football players in the preparatory period - Georgiy Polevoy (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The solution to the issue of developing the physical qualities of young football players can be obtained through the introduction of general physical exercises during the preparatory period of training. The objective is to document the increase in the level of physical fitness of young football players due to specific training. T The statistical analysis was performed using SPSS 20.0 statistical software. The study was conducted for 11 weeks. The children from the CG were engaged in the usual 90-minute lesson program for football players of sports schools. The children in the EG performed various physical exercises to develop certain physical qualities. Results showed that regarding pre-to-post comparisons, for experimental and control groups, better results were recorded after compared with pre-training for running 30 m (p<0.001and p=0.017, respectively), shuttle running (both p<0.001), long jump (both p<0.001), pull-up (both p<0.001), 6min test (both p<0.001) and leaning forward (both p<0.001). Concerning comparisons at post-training between the two groups, the experimental group resulted in better performances than the control in shuttle running (p<0.001), long jump (p<0.001) and leaning forward (p=0.018) as well as for delta change (i.e., the difference between pre and post for each group) in the running 30 m (p<0.001) and 6min test (p<0.001). After athletes from the experimental group performed a special set of physical exercises to develop physical qualities, their performance improved significantly. This indicates the effectiveness of the tools and methods used to develop physical qualities.